Peran UMKM Kain Tenun dalam Memperkuat Ketahanan Ekonomi dan Ketahanan Budaya Nasional di Era Fast Fashion - Donna Aprilia Princessa; Indira Selviana Cahyati; Kurnia Reva Aulia; Ratih Maeychicha Zaskiaji; Septiana Olivia Prihandini (Income Journal Of Economics Development, 2026)
MSMEs have an important role as the foundation of the community's economy as well as the guardian of cultural heritage. This study aims to analyze the role of Ms. Hana's Ikat Ikat Ngorek MSMEs in strengthening national economic and cultural resilience amid the dominance of the fast fashion industry. However, the weaving business faces various challenges, such as the declining interest of the younger generation in woven products and the increasingly fierce market competition. This research uses a qualitative approach with a descriptive-analytical method. Data were obtained through direct observation, in-depth interviews, and literature studies. The collected data were analyzed qualitatively through data reduction, data presentation, conclusion drawing, and triangulation. The results of the study show that Kodok Ngorek Weaving MSMEs contribute to economic resilience through the provision of jobs and increased community income. In addition, this business plays a role in preserving and introducing local cultural identity to the wider community. In facing the challenges of fast fashion, business owners apply various adaptation strategies, such as more modern design innovations, as well as digital marketing optimization through social media. Therefore, the ability to adapt and innovate is an important factor for the sustainability of MSMEs in maintaining economic competitiveness while preserving traditional cultural values in the midst of rapidly changing market trends.